Congenital laryngomalacia: Is it an inflammatory disease? The role of vitamin D. (11th April 2019) - Hassan, Megahed M.; Emam, Ahmed M.; Mahmoud, Ahmed M.; Awad, Al Husseiny; Rezk, Ibrahim; Abou‐Taleb, Ashraf; Mohamed, Montasser M.; El‐Magd, Essam A. A.
Abstract : Objectives/Hypothesis: Laryngomalacia is the most common cause of stridor in infants. The exact pathophysiology is still not well understood. Our objective was to investigate whether laryngomalacia is an inflammatory disease, focusing on the possible role of vitamin D. Study Design: Case‐control study. Methods: Sixty Egyptian infants and 60 mothers were included in this study. They were divided into four equal groups (n = 30 for each): infants with laryngomalacia (LM‐infants), control infants (C‐infants), mothers of the infants with laryngomalacia (LM‐mothers), and mothers of the control infants (C‐mothers). Laryngoscopy was performed and serum 25‐hydroxyvitamin D (25[OH]‐vitamin‐D) and interleukin 6 (IL‐6) were estimated. Results: Significant increase of serum IL‐6 associated with a significant decrease in serum 25(OH)‐vitamin D was observed in the LM‐infants compared to the C‐infants ( P < .001 for both). LM‐mothers had significantly lower 25(OH)‐vitamin D status compared to C‐mothers ( P < .001). Conclusions: Deficiency of 25(OH)‐vitamin D in LM‐infants may result in dysregulation of the immune responses with elevation of a proinflammatory cytokine (IL‐6). Laryngomalacia could be an inflammatory disease due to 25(OH)‐vitamin D deficiency as evidenced by the high level of IL‐6. This finding may open the door to the appropriate prevention, diagnosis, and treatment, especially for moderate to severe laryngomalacia. Level of Evidence: 3b Laryngoscope, 130:448–453, 2020